21st century excitatory amino acid research: A Q & A with Jeff Watkins and Dick Evans. (15th October 2021) - Watkins, Jeffrey C.; Evans, Richard H.; Bayés, Àlex; Booker, Sam A.; Gibb, Alasdair; Mabb, Angela M.; Mayer, Mark; Mellor, Jack R.; Molnár, Elek; Niu, Li; Ortega, Arturo; Pankratov, Yuriy; et al.
Abstract: In 1981 Jeff Watkins and Dick Evans wrote what was to become a seminal review on excitatory amino acids (EAAs) and their receptors (Watkins and Evans, 1981). Bringing together various lines of evidence dating back over several decades on: the distribution in the nervous system of putative amino acid neurotransmitters; enzymes involved in their production and metabolism; the uptake and release of amino acids; binding of EAAs to membranes; the pharmacological action of endogenous excitatory amino acids and their synthetic analogues, and notably the actions of antagonists for the excitations caused by both nerve stimulation and exogenous agonists, often using pharmacological tools developed by Jeff and his colleagues, they provided a compelling account for EAAs, especially l -glutamate, as a bona fide neurotransmitter in the nervous system. The rest, as they say, is history, but far from being consigned to history, EAA research is in rude health well into the 21st Century as this series of Special Issues of Neuropharmacology exemplifies. With EAAs and their receptors flourishing across a wide range of disciplines and clinical conditions, we enter into a dialogue with two of the most prominent and influential figures in the early days of EAA research: Jeff Watkins and Dick Evans. This article is part of the Neuropharmacology Special Issue on 'Glutamate Receptors - The Glutamatergic Synapse'.